Pedagogical contract: social imaginary in democratic evaluative practice - Nellys Marisol Castillo; Ana Mercedes Colmenares (Corporación Universitaria Minuto de Dios, 2017)
This research focused on generating reflection processes that should lead to a collective construction of a pedagogical contract as a participative tool for the assessment practice in our institute. Participant co-researchers are: eighteen Departmental Representatives at the Assessment Unit, Assessment Unit Chairwoman, Students Support Manager, and Curriculum Manager. The participative action research led the approach of the present investigation. Five discussion and co-construction meetings were carried out where assessment criteria were discussed, also the appropriation of theoretical and legal epistemic referents that frame negotiation and participation in the design and implementation of the pedagogical contract at UPEL-IPB were reviewed. As data collection methods, pear observation and discussion teams were used, and as methodological resources, field diaries and audiovisual registers were implemented. Findings are organized in three different aspects: I. Assessment focus, uncertainty and fascination; II. Construction lead way, voice polyphony; III. Pedagogical contract, shared construction. These aspects are framed under the emergence of several categories generally related to models, conceptions, instruction, consequences and assessment performance. A proposal of pedagogical contract was agreed on -including its main elements and its respective implementation policies-. We hope to contribute to the consolidation of a more objective assessment approach -focused on reflective, consensus and negotiation processes- which should guarantee our teachers and students' participation.